Innovation Of Adding Green Mustard To Rice Crackers - Tanius, Billy; Pramudia, Heru; Surjawan, Iwan (Journey : Journal of Tourismpreneurship, Culinary, Hospitality, Convention and Event Management, 2024)
Crackers are a type of dry food that contains quite high starch, made from tapioca flour as a base ingredient. Different spices are added to produce different types of crackers. Crackers can also be innovated by using other ingredient substitutions that aim to add and have functional value, one of which is the addition of green mustard. This research aims to utilize green mustard into an innovative rice cracker product. This is caused by the lack of rice cracker products with vegetables as processed products. This study uses a quantitative approach. Specifically, this research was carried out using the rules of the experimental method which is laboratory research. This research uses quantitative data in the form of formula recipes and results of sensory tests and organoleptic tests. The formula or recipe comes from experimental tests carried out in the laboratory, namely the Bali International Polytechnic kitchen. Meanwhile, organoleptic test data was obtained from research respondents. Experiments in the laboratory and collecting responses from respondents are the primary data sources in this research. Apart from that, this research also uses secondary data sources in the form of literature related to the research topic. This research uses cracker processing theory and culinary product development models as a basis for carrying out research. Based on the results of experiments, rice crackers with the addition of green mustard can be developed into crackers that have a different color, aroma, taste, texture & crunch, as well as a shape from rice crackers in general. Crackers produced using the same method but with the addition of green mustard are more popular in terms of taste, texture, aroma, shape and color, better than rice crackers in general. And this research also found that crackers that have been dried for a long time must be dried again in the hot sun so that the crackers can bloom perfectly.